2023
DOI: 10.1038/s43705-023-00243-7
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Sea heatwaves jeopardize greater amberjack’s (Seriola dumerili) aquaculture productivity through impacts on the fish microbiota

Abstract: Climate change is dramatically increasing the frequency and severity of marine heatwaves (MHWs) in the Mediterranean basin, strongly affecting marine food production systems. However, how it will shape the ecology of aquaculture systems, and the cascading effects on productivity, is still a major knowledge gap. The present work aims to increase our understanding of future impacts, caused by raising water temperatures, on the interaction between water and fish microbiotas, and consequential effects upon fish gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…Meanwhile, Pseudoalteromonas isolates have been generally considered to be involved in predator-like interactions within the microbial loop, and to be used as a defense agent against pathogens in marine fauna [42] . Therefore, the emergence of P. piscicida H2 only in healthy cuttlefish indicated that P. piscicida H2 is healthful for cuttlefish, which is similar to the previous researches that the abundance of members of the Pseudoalteromonas is positively correlated with fish healthy stage [43] . Thus, it could be postulated that the balance of V. alginolyticus H1 and P. piscicida H2 is closely related to the health status of cuttlefish.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, Pseudoalteromonas isolates have been generally considered to be involved in predator-like interactions within the microbial loop, and to be used as a defense agent against pathogens in marine fauna [42] . Therefore, the emergence of P. piscicida H2 only in healthy cuttlefish indicated that P. piscicida H2 is healthful for cuttlefish, which is similar to the previous researches that the abundance of members of the Pseudoalteromonas is positively correlated with fish healthy stage [43] . Thus, it could be postulated that the balance of V. alginolyticus H1 and P. piscicida H2 is closely related to the health status of cuttlefish.…”
Section: Discussionsupporting
confidence: 88%
“…For saltwater fish, alpha diversity increased with a more basic pH, higher salinity, and dO 2 concentration but decreased at higher temperatures. Studies assessing the effect of physicochemical factors on fish skin microbiomes have similarly shown that exposure to high temperatures results in decreases in alpha diversity over time and differences in beta diversity in saltwater greater amberjack ( Seriola dumerili ) (Sánchez-Cueto et al 2023 ) and in chum salmon ( Oncorhynchus keta ) (Ghosh et al 2022 ). Studies on the flag cichlid ( Mesonauta festivus) and black piranha ( Serrasalmus rhombeus) found no effects of pH on skin microbiomes (Sylvain et al 2019 ), however, in Tambaqui ( Colossoma macropomum ) (data included within this study) exposure to a low pH (pH 4.0) compared to control (pH 6.3) resulted in changes in fish skin beta diversity, but not alpha diversity (Sylvain et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been far fewer studies, however, examining the microbiota in fish skin (Gomez and Primm 2021 , Wang et al 2023 , Berggren et al 2022 ). Understanding the composition of fish skin microbiomes and the dynamics in response to environmental conditions will help establish their associations with health and disease (Berggren et al 2022 , Debnath et al 2023 ) and in turn, optimize aquaculture practices (Palladino et al 2021 , Sánchez-Cueto et al 2023 ). To date, there has been relatively little exploration of how skin microbiomes are affected by water physicochemical or biological stressors.…”
Section: Introductionmentioning
confidence: 99%